Characterization of 83Bi209, 74W184, 48Cd112, 30Zn65, 28Ni59 and 26Fe56 using Modified Klein-Nishina formula, for radiation shielding and dosimetry. (February 2021) - Thiele, Katherine T.; Alexander, Raven W.; Maqbool, Muhammad
Abstract: The purpose of the present work is to use Klein-Nishina formula to calculate the electronic cross-sections, atomic cross-section, transfer cross-sections, Compton mass attenuation coefficients and mass-energy transfer cross section of 83 Bi 209, 74 W 184, 48 Cd 112, 30 Zn 65, 28 Ni 59 and 26 Fe 56 when photon beams and γ-ray photons of various energies interact with these elements. The results reveal that all these cross-sections and coefficients are strongly dependent on the energy of photon E and the charge number of the material used. The cross-sections and coefficients decrease with increasing photon energy in the range of 0.284 MeV–7 MeV, and increase with increasing charge number Z or charge number to mass number ratio Z/A. The conclusion describes that fundamental quantities and parameters like Z, E of photon beam and Z/A of these elements can be used and controlled to make them very useful for radiation shielding and protection and radiation dose measurements. Highlights: Use of modified Klein-Nishina formula in studying 83 Bi 209, 74 W 184, 48 Cd 112, 30 Zn 65, 28 Ni 59 and 26 Fe 56 . Investigation of electronic and atomic cross-sections. Investigating Compton mass attenuation coefficients and mass-energy transfer coefficients. Magterials for potential use in radiation shielding and dosimetry.